Long-Term Conservation Agriculture Improves Soil Quality in Sloped Farmland Planting Systems - Hongying Li; Jun Tang; Jing Wang; Jun Qiao; Ningyuan Zhu (Plants)
Conservation agriculture practices (CAs) are important under the increasingly serious soil quality degradation of sloping farmlands worldwide. However, little is known about how the long-term application of CAs influences soil quality at different slope positions. We conducted field experiments for a watershed sloping farmland’s mainstream planting systems in the Three Gorges Reservoir area of China. Orchard plots were treated with a conventional citrus planting pattern (C-CK), citrus intercropped with white clover (WC), citrus orchard soil mulched with straw (SM) and citrus intercropped with Hemerocallis flava contour hedgerows (HF). Crop field plots were treated with a conventional wheat–peanut rotation (W-CK), a wheat–peanut rotation intercropped with Toona sinensis contour hedgerows (TS), a wheat–peanut rotation intercropped with alfalfa contour hedgerows (AF) and a ryegrass–sesame rotation (RS). We collected soil samples from the plots at the upper, middle and lower slope positions and measured their soil properties after a nine-year experiment. We found that (1) CAs improved the soil properties at the three slope positions; (2) the effect of the CAs on the soil properties was more significant than that on the slope position; and (3) the soil quality index at the upper, middle and lower slope positions increased by 29.9%, 45.8% and 33.3%, respectively, for WC; 48.7%, 39.5% and 27.1%, respectively, for SM; and 21.7%, 25.5% and 21.6%, respectively, for HF compared to C-CK; as well as 18.7%, 23.7% and 20.4%, respectively, for TS; 16.9%, 18.6% and 16.5%, respectively, for AF; and 16.1%, 13.0% and 13.9%, respectively, for RS compared to W-CK. These findings suggest that long-term CA application enhances the soil quality of the slope position, of which SM and TS applied to orchards and crop fields, respectively, are the most effective.